Synthesis and characterization of novel amphiphilic biocompatible block-copolymers of poly(N-isopropylacrylamide)-b-poly(L-phenylalanine methyl ester) by RAFT polymerization - Biswas C.S.; Biswas A.; Galluzzi M.; Shekh M.I.; Wang Q.; Ray B.; Maiti P.; Stadler F.J. (My University, 2025)
The synthesis of amphiphilic block-copolymers of poly(N-isopropylacrylamide) (PNIPAM) and poly(N-acryloyl-L-phenylalanine methyl ester) (PNALPA) by RAFT polymerization is reported. The polymers were characterized by proton NMR (1H NMR), gel permeation chromatography (GPC), powder X-ray diffraction (XRD), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA) to understand their structure-property relationships. All synthesized polymers show pH triggered release at acidic (pH 5) and biological pH (pH 7.4). Critical micellar concentration also varied systematically depending on the amphiphilic nature of the polymers. Biocompatibilities of the polymers are also determined to check their suitability for biomedical applications. © 2020 Elsevier Ltd